Practices and Perceptions of Living Donor Liver Transplantation, Nondirected Donation, and Liver Paired Exchange: A National Survey. Issue 5 (26th December 2021) - Kaplan, Alyson; Rosenblatt, Russell; Jackson, Whitney; Samstein, Benjamin; Brown, Robert S.
Abstract : Living donor liver transplantation (LDLT) remains underutilized in the United States. Barriers to LDLT and acceptance of nondirected living liver donation (ND‐LLD) and liver paired exchange (LPE) are unclear. The medical and surgical directors of 99 unique transplantation programs (56 LDLT programs and 43 non‐LDLT programs) were surveyed to gain insight into perceptions and practices of LDLT and types of donors utilized. The response rate was 84%. Most LDLT programs (65%) reported performing ND‐LLD, though opinions regarding allocation and the need for additional evaluation of these donors were mixed. Only a minority of LDLT programs reported performing LPE (12%), but most programs (78%) would be open to cross‐institutional LPE barring logistical barriers. There were significant differences between LDLT and non‐LDLT programs with regard to perceived barriers to LDLT, with LDLT programs reporting mainly donor and recipient factors and non‐LDLT programs reporting institutional factors ( P < 0.001). Understanding perceptions and practices of LDLT, ND‐LLD, and LPE is important to aid in the growth of LDLT.